2010
DOI: 10.1124/mol.110.065953
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Polymorphism in a Forkhead Box A1 (FOXA1) Binding Site of the Human UDP Glucuronosyltransferase 2B17 Gene Modulates Promoter Activity and Is Associated with Altered Levels of Circulating Androstane-3α,17β-diol Glucuronide

Abstract: UDP glucuronosyltransferase 2B17 is present in the prostate, where it catalyzes the addition of glucuronic acid to testosterone and dihydrotestosterone and their metabolites androsterone and androstane-3␣,17␤-diol. Hence, changes in UGT2B17 gene expression may affect the capacity of the prostate to inactivate and eliminate male sex hormones. In this work, we identify a prevalent polymorphism, Ϫ155G/A, in the proximal promoter of the UGT2B17 gene. This polymorphism modulates UGT2B17 promoter activity, because l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
4
21
0
Order By: Relevance
“…Hence, our results show for the first time that FOXA1, a pioneering transcription factor (Lupien et al, 2008), plays a crucial role in controlling basal expression of UGT2B15 in prostate cancer cells. Together with our previous demonstration of the importance of FOXA1 in regulating basal UGT2B17 gene expression (Hu et al, 2010), these findings provide new insights into our understanding of the molecular mechanisms that determine androgen glucuronidation capacity and hence androgen homeostasis and signaling in the prostate. Because UGT2B15 and UGT2B17 are the major enzymes inactivating and eliminating active androgens by glucuronidation, the control of UGT2B15 gene expression by FOXA1 would be of particular significance for individuals homozygous for the UGT2B17 deletion, where UGT2B15 is the only enzyme in the prostate with the capacity to effectively glucuronidate active androgens (McCarroll et al, 2006).…”
Section: Hu and Mackenziesupporting
confidence: 62%
See 2 more Smart Citations
“…Hence, our results show for the first time that FOXA1, a pioneering transcription factor (Lupien et al, 2008), plays a crucial role in controlling basal expression of UGT2B15 in prostate cancer cells. Together with our previous demonstration of the importance of FOXA1 in regulating basal UGT2B17 gene expression (Hu et al, 2010), these findings provide new insights into our understanding of the molecular mechanisms that determine androgen glucuronidation capacity and hence androgen homeostasis and signaling in the prostate. Because UGT2B15 and UGT2B17 are the major enzymes inactivating and eliminating active androgens by glucuronidation, the control of UGT2B15 gene expression by FOXA1 would be of particular significance for individuals homozygous for the UGT2B17 deletion, where UGT2B15 is the only enzyme in the prostate with the capacity to effectively glucuronidate active androgens (McCarroll et al, 2006).…”
Section: Hu and Mackenziesupporting
confidence: 62%
“…We recently reported that FOXA1 is a major regulator of the basal expression of UGT2B17 gene in prostate cancer cell lines (Hu et al, 2010). In this study, we report that FOXA1 is also essential for the basal transcriptional activity of the UGT2B15 gene in LNCaP cells.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…A common genetic polymorphism in the UGT2B17 gene is gene deletion, and evidence shows that individuals who have two deleted UGT2B17 alleles secrete little-to-no urinary testosterone compared to individuals with at least one copy of the gene ( Jakobsson et al, 2006). In addition, a polymorphism in the regulatory region of the UGT2B17 gene has been associated with altered levels of AAG (Hu et al, 2010). While both the UGT2B17 and UGT2B15 polymorphisms are significantly associated with AAG levels in European populations, no observations have been made in individuals of African descent (Hsing, 2001;Swanson et al, 2007;Olsson et al, 2011).…”
mentioning
confidence: 99%
“…A total of 69 published records up to December 15, 2012 were identified, of which 9 were considered potentially eligible for inclusion in this meta-analysis and were retrieved in full texts. Among these, 3 studies were excluded because they had insufficient data on OR calculation [34][35][36]. Finally, 6 articles were included in the meta-analysis.…”
Section: Meta-analysismentioning
confidence: 99%